Tracey Sutton

Register to add an answer

answers: 1

223 cents

Answer:

You need to find the coefficient n if f = (x+1)g.

Replacing f and g by the corresponding equations yields:

`x^3-nx+1 = (x+1)(x^2-x+1)`

You need to open the brackets to the right side:

`x^3- n x+1 = x^3 - x^2 + x + x^2 - x+ 1` =>

=> `x^3- n x+1 = x^3+1`

Equating coefficients of like powers yields:

n = 0

**Evaluating the value of the parameter n yields n = 0.**

68

Deanna Peterson

For answers need to register.

Contacts

mail@expertinstudy.com

Feedback

Expert in study

About us

For new users

For new experts

Terms and Conditions